Satisfaction with nursing care of hospitalized patients: A descriptive, cross-sectional, multicenter study - Plevová, Ilona; Kachlová, Miroslava; Jarošová, Darja; Zeleníková, Renata; Mynaříková, Eva (Medycyna pracy, 2023)
BACKGROUND: In the assessment of healthcare processes focusing on the quality of care provided, patient satisfaction is an important indicator that healthcare providers may use for future setting of healthcare and preventing adverse events. The study aimed to determine satisfaction with nursing care among hospital inpatients. MATERIAL AND METHODS: The sample comprised 14 023 patients staying in medical and surgical wards of 14 acute care hospitals in the Czech Republic in 2019-2020. Data were collected using the Patient Satisfaction Scale, a standardized tool containing 11 items in 3 subscales. Data analysis included descriptive statistics and correlation analysis (Spearman's rank correlation coefficient). RESULTS: Overall, patients reported high satisfaction with nursing care (M = 3.57). Patients were most satisfied with how their technical/rational needs were met (M = 3.57); the least satisfaction was identified in the domain of information needs (M = 3.53). Patients who perceived their health as good (47%) or very good (18%) showed high satisfaction scores (M = 3.77 and M = 3.73, respectively). High scores were also achieved for patients with secondary (M = 3.58) and tertiary (M = 3.59) education, those whose admission was planned (M = 3.59) and those staying in large hospitals (M = 3.60). There were no differences in satisfaction with regard to gender (p = 0.755) and the COVID-19 pandemic (p = 0.190). CONCLUSIONS: Patients' satisfaction with care provided is a highly significant parameter of healthcare quality. It is influenced by a number of aspects which, if adequately defined, may aid in improving the quality of care. Med Pr Work Health Saf. 2023;74(6):461-8.
Keywords: spokojenost pacientů; Patient Satisfaction; pandemie; lidé; Humans; nemocnice; Hospitals; osobní uspokojení; průzkumy a dotazníky; Cross-Sectional Studies; Surveys and Questionnaires; průřezové studie; Personal Satisfaction; Pandemics